Sexual lives and reproductive health outcomes among persons with disabilities: a mixed-methods study in two districts of Ghana - Abdul-Aziz Seidu; Bunmi S. Malau-Aduli; Kristin McBain-Rigg; Aduli E. O. Malau-Aduli; Theophilus I. Emeto (BMC, 2024)
Abstract Introduction People with disabilities (PwDs) constitute a large and diverse group within the global population, however, their sexual and reproductive health (SRH) needs are often neglected, particularly in low-and middle-income countries. This may result in adverse outcomes, such as sexually transmitted infections (STIs), unintended pregnancies, and experience of interpersonal violence (IV). This study aimed to assess the factors that influence the sexual lives of PwDs in two districts of Ghana. Methods A sequential explanatory mixed-methods study design was used to collect data from PwDs. Quantitative data were obtained from 402 respondents using a pretested questionnaire, and qualitative data gathered from 37 participants using in-depth interviews. The quantitative data were analysed using descriptive and inferential statistics, while the qualitative data were analysed using inductive thematic analysis. Results Most PwDs (91%) reported that they have ever had sex, which was associated with age, disability severity, and household size. The prevalence of poor SRH status, STIs, unintended pregnancy, pregnancy termination, and unsafe abortion were 10.5%, 5.7%, 6.4%, 21.6%, and 36.9% respectively. These outcomes were influenced by education, income, health insurance subscription, and proximity to a health facility. The prevalence of IV was 65%, which was related to disability type and severity. The qualitative data revealed five main themes: curiosity to engage in sexual activities, feelings of despair and insecurity with abled partners, preference for sexual relationships with other PwDs, IV and its perpetrators, and adverse SRH outcomes. Conclusion The study findings indicate that most adult PwDs have ever had sex and they face various challenges in their sexual lives. They experience multiple forms of abuse and neglect from different perpetrators at different levels of society, which have negative impacts on their well-being. There is a need for comprehensive and inclusive interventions that address the SRH needs of PwDs, as well as the underlying social and structural factors that contribute to their vulnerability. Further research is recommended to explore the perspectives of stakeholders on how to improve the SRH outcomes of PwDs.